Numerical Analysis of Soil-nailing From Bamboo for Slope Stabilisation Using Plaxis 2D Software - Kamarul Zaman, Ahmad Kamal Zulfikar; Amir Faisal, Amir Nur Rasyid; Rahimi, Muhammad Naqib Naufal; Mat Nor, Ahmad Hakimi (Multidisciplinary Applied Research and Innovation, 2023)
A bare surface of land that has an angle to the horizon is called a slope. This structure of land commonly be subjected to failure when it had a steep slope condition but there are also many causes that lead to its failure. Lately, there have been a lot of slope collapse problems have occurred, resulting in numerous unwanted incidents which some have cost in deaths of life. Those in charge, on the other hand, have grossly misjudged the problem. Slope areas close to public areas and roads should be investigated for stability so that accidents involving the public do not occur. The main objective of this study is to simulate the different soil movements in the slope before and after the application of the soil-nailing from bamboo using Plaxis 2D and to compare the result of the simulation between 2 types of bamboo soil-nailing which is short (3 meters) and long (4 meters). The properties of bamboo and soil are acquired for use in the Plaxis 2D in order to fulfill the study's goal. After that, create a slope modeling in Plaxis 2D and run a simulation with a series of loads totaling 10, 20, 40, and 45 kN. The displayed data are analyzed after the slope's condition has been successfully simulated. The findings of this study indicate that bamboo soil-nailing improves soil stability in terms of safety factors and deformation. The longer bamboo has successfully increased the slope strength, as demonstrated by the comparison with the two types of bamboo soil-nailing. Bamboo has been shown to aid in slope stability, making it a viable alternative to the material currently used in slope stabilizers with a more cost-effective and high-quality product.